Pengaruh Faktor Internal dan Faktor Eksternal Terhadap Harga Saham Perusahaan Sektor Pertambangan di ISSI - Kirana Arenggaraya; Tjetjep Djuwarsa (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This study was made to analyze the influence of both internal and external factors towards stock prices of mining sector companies listed on Indeks Saham Syariah Indonesia (ISSI). Internal factors that used are Return On Assets i(ROA) and Current Ratio (CR), and for the external factors are inflation and Gross Domestic Product (GDP). Stock prices used in this study is stock prices of mining sector companies that consistently listed in ISSI from December 2012 to May 2019. The sample consisted of 17 companies. All of the data were obtained from the official websites of Bursa Efek Indonesia, Bank Indonesia, and the World Bank. Data Panel Regression Analysis is used in this study, using Eviews 11. This study’s results are: partially ROA has a positive and significant influence on stock prices, while partially CR, inflation, and GDP has positive and insignificant influences on stock prices. Simultaneously ROA, CR, inflation, and GDP have a positive and significant influence on stock prices.